A new generalization of Mittag-Leffler function via q-calculus - Nadeem, Raghib; Usman, Talha; Nisar, Kottakkaran Sooppy; Abdeljawad, Thabet (Advances in difference equations, 2020)
The present paper deals with a new different generalization of the Mittag-Leffler function through q -calculus. We then investigate its remarkable properties like convergence, recurrence relation, integral representation, q -derivative formula, q -Laplace transformation, and image formula under q -derivative operator. In addition to this, we consider some specific cases to give the utilization of our main results.